2014
DOI: 10.5812/jjm.13122
|View full text |Cite
|
Sign up to set email alerts
|

GB virus C Viremia and Anti-E2 Antibody Response Among Hemodialysis Patients in Gorgan, Iran

Abstract: Background:GB Virus C is a blood-borne virus and a member of Flaviviridae, like hepatitis C that is distributed globally and puts hemodialysis patients at high risk of developing liver disease. The clinical significance of GBV-C in this population remains unclear.Objectives:The current study aimed to evaluate GBV-C infection among hemodialysis patients.Patients and Methods:Totally, 149 patients receiving hemodialysis were included in the study. The detection of GBV-C sequences in plasma was done by the nested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Generally, the prevalence of HGV varies from 11% to 24%, among HCV-infected individuals (16)(17)(18). The prevalence of HGV infection varies in different regions of Iran and ranges from 3.14% to 10.73% (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the prevalence of HGV varies from 11% to 24%, among HCV-infected individuals (16)(17)(18). The prevalence of HGV infection varies in different regions of Iran and ranges from 3.14% to 10.73% (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we screened samples from whole blood CPDA1, CPDA1 RBC, washed RBC (washed to reduce plasma proteins for reducing the risk of allergic reactions) and leukocyte-reduced RBC (filtered to remove most leukocytes for reducing the risk of febrile transfusion reactions and viral infection, such as cytomegalovirus) products. A high frequency (31.5%) of GBV-C viremia was observed in whole blood or RBC products, which is surprisingly higher than the rate of GBV-C-RNA positivity in healthy blood donors (0.9 to 20%) and high risk individuals (1 to 43.6%), suggesting the likely transmission of the virus via contaminated environmental surfaces (6). The virus was detected in almost all types of RBC components but absent in whole blood CPDA1, which might be related to the small whole blood CPDA1 sample size.…”
Section: Discussionmentioning
confidence: 82%
“…Although the virus has not been clearly linked to any human disease, it has been shown that GBV-C does not replicate in hepatocytes but rather in lymphocytes (1, 8), thus suggesting the possible extrahepatic pathogenicity of the virus (9, 10). There are several reports of an association between GBV-C and hepatitis-associated aplastic anemia besides other hepatitis-causing viruses (3,6,8). In addition, an association between GBV-C and hepatitis B virus (HBV) co-infection and pathogenesis of non-Hodgkin"s lymphoma has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations